New user? Sign up

Existing user? Log in

Main post link -> http://www.facebook.com/photo.php?fbid=3272444470312&l=c9af88f8c1

Note by Uzumaki Nagato Tenshou Uzumaki 5 years, 3 months ago

Easy Math Editor

*italics*

_italics_

**bold**

__bold__

- bulleted- list

1. numbered2. list

paragraph 1paragraph 2

paragraph 1

paragraph 2

[example link](https://brilliant.org)

> This is a quote

This is a quote

# I indented these lines # 4 spaces, and now they show # up as a code block. print "hello world"

2 \times 3

2^{34}

a_{i-1}

\frac{2}{3}

\sqrt{2}

\sum_{i=1}^3

\sin \theta

\boxed{123}

Sort by:

Let S denote the value

Since the integrand is an even function

S = 2 * integrate(0 to infinity) x^2 e^x /(1 + e^x)^2 dx

Apply integration by part, let u = x^2 => du = 2x dx, dv = e^x /(1 + e^x)^2 => v = -1/(1 + e^x)

S/2 = uv - integrate v du

S/2 = -x^2 /(1 + e^x) + 2 integrate(0 to infinity) x/(1 + e^x) dx

Apply the limits from 0 to infinity for -x^2/(1 + e^x), you get 0

S/4 = integrate(0 to infinity) x/(1 + e^x) dx, divide top and bottom by e^x

S/4 = integrate(0 to infinity) xe^(-x) /(1 - (-e^(-x)) dx, this is in the form of a/(1-r), sum of a geometric series

S/4 = integrate(0 to infinity) [ xe^(-x) - xe^(-2x) + xe^(-3x) - xe^(-4x) + ... ] dx

Notice each term follows a Gamma Distribution with alpha = 2, beta = 1/1, 1/2, 1/3, ....

It simplfies to

S/4 = (1/1)^2 - (1/2)^2 + (1/3)^2 - (1/4)^2 + ...

Right hand side is a form of Riemann Zeta function of 2

S/4 = pi^2 /12

S = pi^2 /3

Note that (1/1)^2 - (1/2)^2 + (1/3)^2 - (1/4)^2 + ...

= [ (1/1)^2 + (1/2)^2 + (1/3)^2 + (1/4)^2 + ... ] - 2 [ (1/2)^2 + (1/4)^2 + (1/6)^2 + ... ]

= [ (1/1)^2 + (1/2)^2 + (1/3)^2 + (1/4)^2 + ... ] - (1/2) [ (1/1)^2 + (1/2)^2 + (1/3)^2 + ... ]

= (1/2) * [ (1/1)^2 + (1/2)^2 + (1/3)^2 + (1/4)^2 + ... ]

= (1/2) * pi^2 /6 = pi^2 /12

Log in to reply

may you explain why it can be this.

thx before :D

integrate(0 to infinity) [ xe^(-x) - xe^(-2x) + xe^(-3x) - xe^(-4x) + ... ] dx

= integrate(0 to infinity) [ xe^(-x) ] dx + integrate(0 to infinity) [ xe^(-2x) ] dx + integrate(0 to infinity) [ xe^(-3x) ] dx + integrate(0 to infinity) [ xe^(-4x) ] dx + integrate(0 to infinity) [ xe^(-4x) ] dx + ...

All the integrand are in the form of a gamma function of x^(alpha - 1) * e^(-x/beta)

So alpha = 2 for all integrals, beta = 1/1, 1/2, 1/3, 1/4, ....

@Pi Han Goh – ok :D i very understand it thx you so much :D

Problem Loading...

Note Loading...

Set Loading...

Easy Math Editor

`*italics*`

or`_italics_`

italics`**bold**`

or`__bold__`

boldNote: you must add a full line of space before and after lists for them to show up correctlyparagraph 1

paragraph 2

`[example link](https://brilliant.org)`

`> This is a quote`

Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.`2 \times 3`

`2^{34}`

`a_{i-1}`

`\frac{2}{3}`

`\sqrt{2}`

`\sum_{i=1}^3`

`\sin \theta`

`\boxed{123}`

## Comments

Sort by:

TopNewestLet S denote the value

Since the integrand is an even function

S = 2 * integrate(0 to infinity) x^2 e^x /(1 + e^x)^2 dx

Apply integration by part, let u = x^2 => du = 2x dx, dv = e^x /(1 + e^x)^2 => v = -1/(1 + e^x)

S/2 = uv - integrate v du

S/2 = -x^2 /(1 + e^x) + 2 integrate(0 to infinity) x/(1 + e^x) dx

Apply the limits from 0 to infinity for -x^2/(1 + e^x), you get 0

S/4 = integrate(0 to infinity) x/(1 + e^x) dx, divide top and bottom by e^x

S/4 = integrate(0 to infinity) xe^(-x) /(1 - (-e^(-x)) dx, this is in the form of a/(1-r), sum of a geometric series

S/4 = integrate(0 to infinity) [ xe^(-x) - xe^(-2x) + xe^(-3x) - xe^(-4x) + ... ] dx

Notice each term follows a Gamma Distribution with alpha = 2, beta = 1/1, 1/2, 1/3, ....

It simplfies to

S/4 = (1/1)^2 - (1/2)^2 + (1/3)^2 - (1/4)^2 + ...

Right hand side is a form of Riemann Zeta function of 2

S/4 = pi^2 /12

S = pi^2 /3

Note that (1/1)^2 - (1/2)^2 + (1/3)^2 - (1/4)^2 + ...

= [ (1/1)^2 + (1/2)^2 + (1/3)^2 + (1/4)^2 + ... ] - 2 [ (1/2)^2 + (1/4)^2 + (1/6)^2 + ... ]

= [ (1/1)^2 + (1/2)^2 + (1/3)^2 + (1/4)^2 + ... ] - (1/2) [ (1/1)^2 + (1/2)^2 + (1/3)^2 + ... ]

= (1/2) * [ (1/1)^2 + (1/2)^2 + (1/3)^2 + (1/4)^2 + ... ]

= (1/2) * pi^2 /6 = pi^2 /12

Log in to reply

may you explain why it can be this.

Notice each term follows a Gamma Distribution with alpha = 2, beta = 1/1, 1/2, 1/3, ....

thx before :D

Log in to reply

integrate(0 to infinity) [ xe^(-x) - xe^(-2x) + xe^(-3x) - xe^(-4x) + ... ] dx

= integrate(0 to infinity) [ xe^(-x) ] dx + integrate(0 to infinity) [ xe^(-2x) ] dx + integrate(0 to infinity) [ xe^(-3x) ] dx + integrate(0 to infinity) [ xe^(-4x) ] dx + integrate(0 to infinity) [ xe^(-4x) ] dx + ...

All the integrand are in the form of a gamma function of x^(alpha - 1) * e^(-x/beta)

So alpha = 2 for all integrals, beta = 1/1, 1/2, 1/3, 1/4, ....

Log in to reply

Log in to reply